Work related musculoskeletal symptoms; exposures and perception towards physiotherapeutic interventions at work setting in teachers and caregivers of special schools in Pune: a questionnaire based study - Jadhav, Rujula S.; Berry, Aditi K. (International Journal Of Community Medicine And Public Health, 2023)
Background: Teachers and caregivers at special schools are at a risk of developing work related musculoskeletal disorders (WRMSDs) as they tend to work in awkward postures. It is important to identify musculoskeletal complaints and exposure levels to incorporate work site modifications to reduce risk of developing WRMSDs. Also understanding their perception towards physiotherapy might help in better implementation of worksite wellness programs. Methods: Participants were administered nordic musculoskeletal questionnaire (NMQ), quick exposure check (QEC) questionnaire and a self-designed questionnaire with five domains. Results: Out of the 66 participants, 36 were teachers and 30 were caregivers. Results of NMQ stated that, 20 participants reported to have pain. 50 participants had discomfort in the form of stiffness, fatigue. Assessment via QEC revealed, 39 participants were exposed at a lower level, followed by 22 and 5 who were exposed at moderate and higher level of the risk factors causing WRMSDs respectively. 26 participants were not engaged in regular physical activity. 26 participants had never been explained about safe and ideal ways to handle children with special needs in order to prevent WRMSDs. Conclusions: Musculoskeletal pain was predominantly in the lower back, shoulder/arms, and neck region. Almost 60% of participants were exposed at a lower level to the risk factors leading to WRMSDs. All of the participants stated that they would like to attend a training program by a physiotherapist regarding the same.